2004
DOI: 10.1016/j.ijdevneu.2004.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Is autism due to brain desynchronization?

Abstract: The hypothesis is presented that a disruption in brain synchronization contributes to autism by destroying the coherence of brain rhythms and slowing overall cognitive processing speed. Particular focus is on the inferior olive, a precerebellar structure that is reliably disrupted in autism and which normally generates a coherent 5-13 Hz rhythmic output. New electrophysiological data reveal that the continuity of the rhythmical oscillation in membrane potential generated by inferior olive neurons requires the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 66 publications
(75 reference statements)
4
67
0
4
Order By: Relevance
“…6 The role of per1 in modulating high-frequency oscillators concerned with communicative timing, [69][70][71] together with our findings of association of per1 with autistic disorder, strengthens the notion that temporal deficits are quintessential to autistic disorder. [21][22][23][24][25][26]28,29,39 Purkinje neurons are important for learning appropriate timing 120,121 and their abnormally low number in the cerebella of autistic subjects 115,122 is considered a keystone biological observation implicating cerebellar dysfunction. 123,124 In this context, reports of a per1 interacting protein (PIPS) in rat that co-translocates with per1 into the nucleus 125 and which is further shown to be required for neuronal growth factor-mediated neuronal survival in P12 cells, 126 tentatively suggests a role for per1 in the lack of Purkinje neurons of the cerebellum in autism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The role of per1 in modulating high-frequency oscillators concerned with communicative timing, [69][70][71] together with our findings of association of per1 with autistic disorder, strengthens the notion that temporal deficits are quintessential to autistic disorder. [21][22][23][24][25][26]28,29,39 Purkinje neurons are important for learning appropriate timing 120,121 and their abnormally low number in the cerebella of autistic subjects 115,122 is considered a keystone biological observation implicating cerebellar dysfunction. 123,124 In this context, reports of a per1 interacting protein (PIPS) in rat that co-translocates with per1 into the nucleus 125 and which is further shown to be required for neuronal growth factor-mediated neuronal survival in P12 cells, 126 tentatively suggests a role for per1 in the lack of Purkinje neurons of the cerebellum in autism.…”
Section: Discussionmentioning
confidence: 99%
“…Newson 22 ), with hypotheses encompassing circadian, communicative and/or neurological aspects of timing. 21,[23][24][25][26][27][28][29] For example, Boucher 25 suggests a core timing deficit presenting different manifestations by its effect on the elements of an integrated system of neural and physiological oscillators. Wimpory et al 21 hypothesize a causative, concurrent and developmental role 30 for timing deficit in autistic disorder and that this deficit is derived from pathological variations in the structure/ function of clock/clock-related genes.…”
Section: Timing Difficulties and Autismmentioning
confidence: 99%
“…In a paradigm of operant conditioning, it was found that distributed activity among subsets of 20-30 CFs was phase-locked to a rhythmic movement at Ϸ7 Hz (30). We have recently suggested that an evoked oscillation through the CF system may scale a CS-US interval into units of motor time to optimize the learned timing and expression of a movement during classical conditioning (31). Further experiments are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been suggested that timing of fast movement and modulation of cerebellar output during movement is accomplished by rhythmic and synchronized firing of ensembles of olivary neurons and their population code rather than individual neuronal oscillations (Welsh et al, 1995;Welsh, 2002). Welsh et al (2005) further hypothesized that disorders such as autism may be explained by inferior olive dysfunction resulting in impairment of temporal processing and reaction to fast sensory input.…”
Section: Introductionmentioning
confidence: 99%